Design of SCADA Wireless System Protocol-Based AX.25 for Monitoring Micro hydro Power Plants - Salahuddin Salahuddin; Yusman Yusman; Bakhtiar Bakhtiar; Fadhli Fadhli (Journal of Multidisciplinary Academic, 2017)
With a range of long distances or depths and areas beyond the reach of the internet it is necessary to design a wireless SCADA system based on the AX.25 protocol for the purpose of monitoring Micro hydro power generation and forming a prototype in a model of a micro hydro power plants (Micro hydro power plant) wirelessly monitoring system. The method used in this research is quantitative method, by designing a system to monitor Micro hydro power plant wirelessly by utilizing AX.25 protocol. This system can monitor several Micro hydro power plant parameters such as voltage, current and frequency and turbine rotation so that it can be accessed directly at one central location. Data transmitted by Remote Terminal Units (RTUs) may serve as a reference for operators to decide on further steps if any monitored Micro hydro power plant parameters change from a predetermined standard. This prototype has been simulated using the Proteus 8.6 and LabView 2012 software. Data from the sensors transmitted over radio frequency using KYL 1020 from each RTU to MTU and connected to the computer using LabView software and displayed on the computer with taking into account the operating parameters, characteristics and workings of the AX protocol. The RTU system has been successfully simulated using 2 ACS712 current sensors, voltage sensor, zero crossing point, frequency sensor and rotation sensor functional for monitoring Micro hydro power plant parameters. The AX.25 protocol has been applicable in the wireless SCADA network for monitoring the performance of the Micro hydro power plant by embedding in a KYL-1020UA transceiver radio using the 433 MHz frequency and the AFSK modulation system. Radio transmitter KYL-1020UA has been successfully simulated to send data from sensors to display on the computer through SCADA built applications. The data changes in the RTU section can be displayed properly on the GUI in accordance with the existing display at the Micro hydro power plant location.